2021
DOI: 10.1007/s12149-021-01580-0
|View full text |Cite
|
Sign up to set email alerts
|

[18F]FDG PET/MRI in rectal cancer

Abstract: We conducted a systematic literature review on the use of [18F]FDG PET/MRI for staging/restaging rectal cancer patients with PubMed, Scopus, and Web of Science, based on the PRISMA criteria. Three authors screened all titles and abstracts and examined the full texts of all the identified relevant articles. Studies containing aggregated or duplicated data, review articles, case reports, editorials, and letters were excluded. Ten reports met the inclusion criteria. Four studies examined T staging and one focused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 30 publications
(96 reference statements)
0
25
0
Order By: Relevance
“…The systematic review of Crimì et al in 2021 revealed that the reported sensitivity of T staging in [18F] FDG PET/MRI was in the range of 94-100%, specificity 73-94%, and accuracy 92-100%. The reported sensitivity, specificity, and accuracy for N staging were 90-93%, 92-94%, and 42-92% accordingly [53].…”
Section: Positron Emission Tomography/magnetic Resonance Imaging (Pet/mri)mentioning
confidence: 99%
“…The systematic review of Crimì et al in 2021 revealed that the reported sensitivity of T staging in [18F] FDG PET/MRI was in the range of 94-100%, specificity 73-94%, and accuracy 92-100%. The reported sensitivity, specificity, and accuracy for N staging were 90-93%, 92-94%, and 42-92% accordingly [53].…”
Section: Positron Emission Tomography/magnetic Resonance Imaging (Pet/mri)mentioning
confidence: 99%
“…As some exam-ples, the conjugation of 99mTc with silica [202], iron oxide [203] or gold [204] NPs was exploited for SPECT/MRI or SPECT/CT imaging of tumors in preclinical mouse models. Likewise, the conjugation of 18F with iron oxide NP was found effective for dual imaging with PET/MRI of stem cell biodistribution [205] as well as for monitoring anti-angiogenic therapeutic effects in breast cancer xenograft mouse models [206] and diagnosis of rectal cancer in clinics [207]. Importantly, since PET/MRI systems have become operational worldwide, several imaging protocols involving the use of 18F for whole body scanning in oncology are currently under standardization for patient management in clinics [208].…”
Section: In Vitro and In Vivo Tracking Of Np Deliverymentioning
confidence: 99%
“…The combination of morphological, functional and metabolic information in the same test has raised this new technique as a possible "one-stop-shop" tool in oncological imaging that can aid in the diagnosis and clinical management of oncologic patients with a lower biological cost. In the clinical setting, PET/MRI was primarily used for prostate cancer, neuro-oncological diseases, soft-tissue sarcomas, colorectal cancer, pediatric malignancies and in cases of persistent clinical suspicion of abdominal malignancy with negative imaging findings [15,16].…”
mentioning
confidence: 99%